The Improvement of Family Coping in Taking Care of Patient Mental Disorder with Spiritual Therapy; Direction, Obedience and Acceptance (Doa) - Ah. Yusuf; Suhartono Taat Putra; Yusti Probowati (Universitas Airlangga, 2012)
Introduction: Mental disorder remains a stigma in society, even until now. A family who have a member with mental disorder, will experience continues objective and subjective burden, experience serious stress for a lifetime, which may cause ineffective coping.Method: Design used in this study was experimental (pre post test control group design). The population was every family of patient with mental disorder in Menur Mental Hospital along the year of 2010, has been taking care there twice, in minimum, lived in Surabaya. The samples were chosen by allocation simple random. Samples were 13 persons in each treatment and control group. The intervention was given in 60–120 minute in 8 times meeting with average interval about 1 week. Data analysis was done using paired t-test and independent t-test.Result: Results in this study showed that there was signiﬁcant change in total of family coping (p = 0.040), maintaining family integration, cooperation and an optimistic deﬁnition of the stuation (p = 0.009), maintaining social support, self esteem, and psychological stability (p = 0.230), understanding the medical situations through communication with other parents and concultation with medical staff (p = 0.025).Discussion: The provision of family therapy with spiritual approach (DOA) can increase family coping in taking care of patient with mental disorder.